Prevalence of Cryptococcal Infection among HIV Infected Patients Attending a Tertiary Hospital in South-west Nigeria - Ibijola, Ajayi Adeleke; Adewumi Bakare; Ajetunmobi, Wasiu Adegbenga; Awoyinka, Babatunde Sunday; Bamiteko, Oluwatoyin Temitope; Ugwueze, Chinecherem Gloria; Esan, Ayodele Jacob; Adegbamigbe, Oluwafemi Johnson; Fasakin, Kolawole Asimiyu; Bamisaye, Olanrewaju Sola (British Journal of Healthcare and Medical Research, 2026)
Background: Cryptococcal infection is a fungal infection often found in immunocompromised patients like HIV – AIDS. The infection is found in 2-7 cases per 100,000 of HIV – AIDS patients with a 12% fatality in USA. Approximately 625,000 deaths globally are reported yearly from cryptococcal infection. Sub – Saharan Africa has been reported to have the highest Cryptococcal infection mortality in HIV – AIDS patients annually. Aim: This study was conducted to determine the prevalence of Cryptococcal infection among HIV infected patients attending a tertiary Hospital in Nigeria to serve as a template for the necessary interventions required to combat the menace of the high morbidity and mortality associated with Cryptococcal infection in people living with HIV-AIDS. Materials and Method: This is a retrospective cross- sectional review of a 5 years (2021-2025) hospital records. A pro forma was used in collecting data from the hospital records. Analysis was done using descriptive statistical tool of the statistical package of social sciences version 27 to obtain frequency, percentages and bar chart while T- test was used to obtain P values for incidence of Cryptococcal infection and gender distribution among the study population. The level of statistical significance was set at a predetermined P< 0.05. Results: The prevalence of cryptococcal infection among the HIV infected patients in this study was 11.8% which indicates that more than one in ten patients in this cohort had evidence of Cryptococcal infection, reflecting a considerable burden in the population. A statistically significant difference (P= 0.017) of Cryptococcal infection was found by gender with higher seroprevalence of 16.7 in female compared to 4.8% in males suggesting a gender based disparity in infection risk within the cohort. Conclusion: Cryptococcal infection is a very relevant opportunistic infection among HIV –infected patients in Nigeria with overall prevalence of 11.8 percent with statistically significant association with gender, females having higher prevalence.